Revolutionary negotiations : Indians, empires, and diplomats in the founding of America - Sadosky, Leonard J. (Jeffersonian America., 2009)
"Revolutionary Negotiation examines early American diplomatic negotiations with both the European powers and the various American Indian nations from the 1740s through the 1820s. Leonard J. Sadosky interweaves previously distinct settings for American diplomacy - courts and council fires - into a single transatlantic system of politics." "Whether states were functioning as provinces in the British Empire or as independent states, American assertions of power were directed simultaneously to the west and to the east - to Native American communities and to European empires across the Atlantic. American leaders aspired to equality with Europeans, who often dismissed them, while they were forced to concede agency to Native Americans, whom they often wished they could ignore. As Americans used diplomatic negotiation to assert their new nations equality with the great powers of Europe and gradually defined American Indian nations as possessing a different (and lesser) kind of sovereignty, they were also forced to confront the relations between the states in their own federal union." "Acts of diplomacy thus defined the founding of America - not only by drawing borders and facilitating commerce, but also by defining and constraining sovereign power in a way that privileged some and weakened others. These negotiations truly were revolutionary."--Jacket